Penerapan Supervisi Akademik Teknik Individual Kunjungan Kelas untuk Meningkatkan Kemampuan Guru Mengembangkan Pendekatan Pembelajaran di SDN 103/X Sidomukti Semester Ganjil Tahun Ajaran 2021/2022 - Junaidi Junaidi (Journal on Education, 2022)
The purpose of this study was to obtain information and discuss the application of academic supervision of individual class visits to improve the ability of teachers to develop learning approaches at SDN 103/X Sidomukti in the odd semester of the 2021/2022 academic year. This research is a school action research which consists of two cycles where each cycle follows four stages, namely planning, implementation, observation and reflection. This research was carried out at SDN 103/X Sidomukti in the odd semester of the 2021/2022 academic year with 6 teachers as the subject of SDN 103/X Sidomukti. Data collection techniques using observation sheets, field notes, and documentation. Data were analyzed using percentages and data reduction. The results of the study indicate that through academic supervision, teachers can improve the ability of teachers in developing learning approaches at SDN 103/X Sidomukti by giving rewards.